2012
DOI: 10.1016/j.bone.2011.12.022
|View full text |Cite
|
Sign up to set email alerts
|

The ubiquitin E3 ligase WWP1 decreases CXCL12-mediated MDA231 breast cancer cell migration and bone metastasis

Abstract: Advanced breast cancers preferentially metastasize to bone where cells in the bone microenvironment produce factors that enhance breast cancer cell homing and growth. Expression of the ubiquitin E3 ligase WWP1 is increased in some breast cancers, but its role in bone metastasis has not been investigated. Here, we studied the effects of WWP1 and itch, its closest family member, on breast cancer bone metastasis. First, we immunostained a multi-tumor tissue microarray and a breast cancer tissue microarray and dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 43 publications
2
29
1
Order By: Relevance
“…Lee et al (2013) reported that WWP1 interacted with AMPK and downregulated its expression through ubiquitin ligase activity in skeletal muscle [32]. Subik et al (2012) demonstrated that WWP1 functioned as an inhibitor of breast cancer metastasis to bone by negatively regulating CXCL 12-induced lysosomal degradation of CXCR4 [33]. In this study, we show for the first time that WWP1 plays an important role in TLR-mediated inflammation as an E3 ubiquitin ligase.…”
Section: Discussionsupporting
confidence: 55%
“…Lee et al (2013) reported that WWP1 interacted with AMPK and downregulated its expression through ubiquitin ligase activity in skeletal muscle [32]. Subik et al (2012) demonstrated that WWP1 functioned as an inhibitor of breast cancer metastasis to bone by negatively regulating CXCL 12-induced lysosomal degradation of CXCR4 [33]. In this study, we show for the first time that WWP1 plays an important role in TLR-mediated inflammation as an E3 ubiquitin ligase.…”
Section: Discussionsupporting
confidence: 55%
“…Indeed, many published studies have described various consequences of the WWP1-induced ubiquitination depending on the substrates, including proteasomal degradation, lysosomal degradation, subcellular redistribution, and transcriptional activity (5,22,23,30,31). Here, we found that WWP1 conjugated its polyubiquitination mainly through Lys-63 polyubiquitin chains, although we could clearly detect Lys-48-linked polyubiquitination.…”
Section: Discussioncontrasting
confidence: 50%
“…WWP1 depletion led to increased cell migration towards a CXCL12 gradient, as well as reduced CXCL12-induced CXCR4 lysosomal trafficking and degradation, suggesting that WWP1 targets CXCR4 to lysosome-mediated destruction, although a more detailed mechanism remains to be elucidated. Mice inoculated with the breast cancer cells stably depleted of WWP1 showed more osteolytic lesions and significantly increased tumor area in bone marrow [138]. Overall, these findings suggest negative correlation between WWP1 level and bone metastasis in metastatic breast cancer, highlighting WWP1 as a potential biomarker and/or target of the disease.…”
Section: Wwpsmentioning
confidence: 80%